Modelagem e análise experimental do escoamento de esferas macias em fluidos viscosos: estudo de colisões partícula-partícula e partícula-superfície e da interação partícula-fluído - Melo, Karla Raphaela Braga de (Universidade Federal de São Carlos, 2020)
Solid-fluid flows are widely used in chemical, biochemical, food and petroleum processes. These include crystallization and sedimentation steps, hydrometallurgical operations, backwashing of granular filters, adsorption and ion exchange, effluent treatment, among others. In these processes, particle or particle-surface collision influences the fluid dynamics and energy dissipation resulting from collisions, and therefore understanding the behavior of particles in this type of flow is critical to improving process and equipment efficiency. In this context, this work investigated particle-particle and particle-surface collisions in solid-fluid flows, with emphasis on low mechanical strength particles, considered soft particles. For this, particles with different elastic, superficial and physical properties were characterized for density, diameter, roughness and Young’s modulus. As hard particles, ABS (coated and uncoated), Fluorelastomer and Nitrile spheres were used, while soft particles were synthesized from sodium alginate solutions in cationic chloride solutions (Ca2+, Ba2+ and Co2+). The interactions resulting from particle-surface and particle-particle collisions were experimentally analyzed from restitution coefficient measurements on pendulum-type equipment. The results showed influence of surface and elastic properties on the coefficient, showing a decreasing tendency of this parameter with the increase of the collision velocity, more significant on the soft particles, and with the decrease of Young’s modulus. From the experimental observations, a regression model was proposed for each particle group in order to predict the coefficient of restitution. In addition to the pendulum, the influence of the impact velocity on the coefficient of ABS spheres was also evaluated from free fall experiments. There was little influence of the impact velocity on the coated balls and greater proximity between the results obtained for the two measurement methods for uncoated ABS balls. Water experiments were also performed, in which significantly lower effective restitution coefficient values were obtained, showing the effect of dissipative viscous forces at the moment of collision. Finally, coefficient values from the literature were tested in simulations using Computational Fluid Dynamics and the Discrete Element Method. The results showed that simulations satisfactorily described the particle collisions behavior with distinct elastic properties.
Modeling and experimental analysis of the flow of soft spheres in viscous fluids: study of particle-particle and surface-particle collisions and particle-fluid interaction
Keywords: Escoamento sólido-líquido; Colisões; Coeficiente de restituição; Coeficiente de restituição efetivo; Fluidodinâmica computacional; Solid-liquid flow; Collisions; Coefficient of restitution; Effective coefficient of restitution; Computational fluid dynamics; ENGENHARIAS::ENGENHARIA QUIMICA